Pengaruh Spending Self-Control dan Fintech Payment Terhadap Manajemen Keuangan Pribadi (Studi Kasus: Mahasiswa Universitas Teknologi Digital) - Khoeriyah, Siti Sa’adah; Manjaleni, Rola (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2025)
This study evaluates the impact of Spending Self Control and Fintech Payment on personal financial management of students at Universitas Teknologi Digital. Spending Self Control refers to an individual's ability to limit spending to avoid unplanned consumer behavior, while Fintech Payment is a means of digital financial transactions carried out via the internet. The approach applied is quantitative, with information collection techniques carried out through questionnaires. The research findings indicate that both variables contribute significantly to personal financial management, both separately and together. However, there are other elements outside the scope of this study that also play a role in influencing students' financial behavior. Therefore, further research is recommended to include a wider number of participants and consider additional variables to obtain a more in-depth picture. Students are advised to use Fintech Payment carefully, control spending in a disciplined manner, and strengthen Spending Self Control by reducing the tendency to shop impulsively and making a budget plan that is in accordance with actual needs.